Pectin functionalized with Cu/Fe nanoparticles for enhanced degradation of methylene blue from wastewater - Hassan, Faiza; Talib, Usama; Saif, Sadia; Akhter, Parveen; Ali, Faisal; Abbas, Moneeza; Younas, Umer; Ashraf, Kamran; Alamri, Saud; Zaman, Qamar uz (Frontiers in Sustainable Food Systems, 2024)
Introduction In the present study, citrus pectin-stabilized copper/iron bimetallic nanoparticle (NP) catalyst has been used for the degradation of methylene blue (MB) dye in wastewater produced from the food industry. Methods The P@Cu/Fe composites were synthesized by co-precipitation and the sol–gel methods. Results and discussion The characterization of the composites was carried out using UV, FTIR, SEM, and XRD techniques, revealing that P1@Cu/FeNPs synthesized through co-precipitation had a particle size of 150–35 nm with an irregular spherical and hexagonal shape. P2@Cu/FeNPs, synthesized using the gel combustion method using triethylamine as fuel, proved to be a better nanocatalyst with spherical particles having a uniform structure and size distribution of 105–23 nm. The mean zeta potential value of P1@Cu/FeNPs was found to be between 0 and 5mv, showing the composite to be less stable and 13 mv for more stable P2@Cu/FeNPs. The degradation of MB by P1@Cu/FeNPs was recorded up to 23.57% after 35 min and the nanocomposite synthesized by the sol–gel method exhibited 97.28% degradation in 30 min. The P2@Cu/FeNPs performed the best degradation due to their synergistic impact. In essence, this research represents a step toward the synthesis of bimetallic NPs using a biomaterial (citrus pectin) with improved synergistic photocatalytic potential that can induce different features in nanomaterials. Pectin-functionalized NPs using different metals should be synthesized and tested for different catalytic applications.